2018
DOI: 10.1002/jsfa.8861
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a packing medium with alga Bifurcaria bifurcata extract on canned Atlantic mackerel (Scomber scombrus) quality

Abstract: A preservative effect derived from the use of an aqueous B. bifurcata extract as packing medium is concluded, and this result is primarily linked to the presence of hydrophilic preservative molecules. The packing system proposed in this work constitutes a novel and promising strategy to enhance the quality of commercial canned fish products. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
24
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 46 publications
13
24
1
1
Order By: Relevance
“…Consequently, an inhibitory effect on lipid oxidation development is inferred for this alga extract. In agreement to the current research, Barbosa et al showed an inhibitory effect on the FR value in canned Atlantic mackerel ( S. scombrus ) by including B. bifurcata extracts in the water‐packing medium. A lower FR value was also observed in canned sardine ( S. pilchardus ) that was previously stored under slurry ice conditions when compared to traditional ice …”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Consequently, an inhibitory effect on lipid oxidation development is inferred for this alga extract. In agreement to the current research, Barbosa et al showed an inhibitory effect on the FR value in canned Atlantic mackerel ( S. scombrus ) by including B. bifurcata extracts in the water‐packing medium. A lower FR value was also observed in canned sardine ( S. pilchardus ) that was previously stored under slurry ice conditions when compared to traditional ice …”
Section: Resultssupporting
confidence: 92%
“…In agreement to the present results, TVB‐N levels did not provide differences in canned Atlantic mackerel ( Scomber scombrus ) that was water‐packed under different concentrations of alga B. bifurcata . Opposite results were obtained when an oil‐packing medium was concerned.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations